Fault detection for PMSM motor drive systems by monitoring inverter input currents - Li, Jing; Sumner, M.; Zhang, He; Arellano-Padilla, J. (China Electrotechnical Society ; Institute of Electrical Engineering of the Chinese Academy of Sciences, 2017)
This paper has proposed a fault detecting method for DC supplied permanent magnet synchronize motor (PMSM) drive systems by monitoring the drive DC input current. This method is based on the fault signal propagation from the torque disturbance on the motor shaft to the inverter input currents. The accuracy of this fault signal propagation is verified by the Matlab simulation and experiment tests with the emulated faulty conditions. The feasible of this approach is shown by the experimental test conducted by the Spectra test rig with the real gearbox fault. This detection scheme is also suitable for monitoring other drive components such as the power converter or the motor itself using only one set of current transducers mounted at the DC input side.